2010
DOI: 10.1002/adma.200903120
|View full text |Cite
|
Sign up to set email alerts
|

Solvent‐Stabilized Photoconductive Metal Phthalocyanine Nanoparticles: Preparation and Application in Single‐Layered Photoreceptors

Abstract: This article features solvent-stabilized nanoparticles of photoconductive metal phthalocyanines (MPcs) with small particle sizes and narrow size distributions, which are tractable building blocks for photoelectric devices. The preparation and stabilization mechanism of 1,2-dichloroethane (DCE)-stabilized oxovanadium phthalocyanine (VOPc) and oxotitanium phthalocyanine (TiOPc) nanoparticles are discussed. It is found for the first time that the DCE-stabilized TiOPc and VOPc nanoparticles are positively charged … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
26
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 22 publications
0
26
1
Order By: Relevance
“…Stable colloidal solution of Y‐TiOPc NPs with a concentration up to 100 g L −1 could be obtained by ultrasonically dispersing the prepared Y‐TiOPc powder in 1,2‐dichloroethane or 1,2‐dichlorobenzene, which is helpful for solving the problem of low solubility of TiOPc in organic solvents. Zeta potential of the colloidal Y‐TiOPc NPs in DCE was measured to be +45 mV, which was smaller than that of previously reported II‐TiOPc NPs (+66 mV),24 suggesting that the electron transfer tendency from Y‐TiOPc NPs to DCE is weaker than that from II‐TiOPc NPs to DCE. This is in accordance with the work functions of Y‐TiOPc NPs (5.35 eV) and II‐TiOPc NPs (5.13 eV), as measured in this work with a photoelectron spectrometer surface analyzer (Model AC‐2, Riken Keiki Co.).…”
contrasting
confidence: 75%
See 1 more Smart Citation
“…Stable colloidal solution of Y‐TiOPc NPs with a concentration up to 100 g L −1 could be obtained by ultrasonically dispersing the prepared Y‐TiOPc powder in 1,2‐dichloroethane or 1,2‐dichlorobenzene, which is helpful for solving the problem of low solubility of TiOPc in organic solvents. Zeta potential of the colloidal Y‐TiOPc NPs in DCE was measured to be +45 mV, which was smaller than that of previously reported II‐TiOPc NPs (+66 mV),24 suggesting that the electron transfer tendency from Y‐TiOPc NPs to DCE is weaker than that from II‐TiOPc NPs to DCE. This is in accordance with the work functions of Y‐TiOPc NPs (5.35 eV) and II‐TiOPc NPs (5.13 eV), as measured in this work with a photoelectron spectrometer surface analyzer (Model AC‐2, Riken Keiki Co.).…”
contrasting
confidence: 75%
“…UV–vis absorption spectra measurements (Figure 1b) revealed that in the Y‐TiOPc/DCE colloidal solution, there established an equilibrium between Y‐TiOPc NPs (characterized by the broad absorption band centered at 800 nm) and a small quantity of free TiOPc molecules dissolved in DCE (< 2 mg L −1 , characterized by the sharp absorption peak centered at 690 nm and two small peaks at 621 nm and 659 nm, respectively). The stabilization mechanism of the Y‐TiOPc NPs in DCE could be attributed to the electrostatic repulsion between the NPs and the solvation of the NPs’ surfaces 24…”
mentioning
confidence: 99%
“…Further, nanoarchitectures of organic materials offer additional opportunities to conventional materials for diverse applications, including solid‐state lighting, solid‐state lasers, biophotonics, photodynamic therapy, etc . Nanostructures of MPcs may possess competitive properties such as good dispersibility, high surface area, high reactivity and flexibility . Many known synthetic procedures to prepare MPc nanostructures are based on top‐down approaches and self‐assembly.…”
Section: Introductionmentioning
confidence: 99%
“…Many known synthetic procedures to prepare MPc nanostructures are based on top‐down approaches and self‐assembly. Varied types of morphologies can be obtained by different methods such as the use of surfactants to yield a spherical morphology, electrodeposition of MPcs to obtain rod‐like structures and annealing of evaporated films to obtain ribbon‐like morphology . Other methods of synthesizing MPc nanostructures include laser ablation technique, hydrothermal and solvothermal synthesis .…”
Section: Introductionmentioning
confidence: 99%
“…Titanyl phthalocyanine is a well-known organic photoconductor which shows very good photoconductivity, excellent photostability, and wide absorption in the visible region with high absorbance. 2,[23][24][25] Until now several substituted titanyl and vanadyl phthalocyanines were obtained. [26][27][28] However, the molecular structure was determined for unsubstituted titanyl and vanadyl phthalocyanines only using the Rietveld method on powdered samples 29,30 or crystals, 31 respectively.…”
Section: Introductionmentioning
confidence: 99%